Disparities in access to reperfusion therapies among patients with STEMI of the non-metropolitan and metropolitan region of Aracaju (Research, Society and Development, 2022)
Aim: To compare the celerity of hospital access with percutaneous coronary intervention (PCI), use of primary PCI and 30-day mortality among patients with STEMI who initiated symptoms in the non-metropolitan region with those who started in the metropolitan region of the state of Aracaju. Method: A quantitative cohort study using data from the VICTIM registry from December 2014 to October 2017. A significance level of 5% was adopted (p